PENGARUH KOMPOSISI MEDIA PEMBIBITAN DAN DOSIS PUPUK NPK PADA PERTUMBUHAN BIBIT JARAK PAGAR (Jatropha curcas L.) DENGAN PENYAMBUNGAN - Sugiatno Sugiatno; Herawati Hamim (Universitas Lampung, 2009)
The objective of this research are to know the effect of blend of cattle manure, hull of rice, and soil as nursery medium and NPK fertilizer dosage on growth of physic nut seedling by grafting. The experiment has been conducted in Bandar Lampung from January to June 2008. Is a factorial experiment (3X4) with randomized completely block design, the first factors were nursery medium composition consisted of cattle manure, soil, and hull of rice, with volume ratio 3:1:1, 1:1:1, and 1:1:3. The second factors are NPK fertilizer dosage consisted of 0, 1, 3, and 5 g/seedling. The treatments were consisted 3 replication and each experiment unit consisted 10 seedlings. The results show that (1) blend of cattle manure, soil, and hull of rice with ratio 1:1:3 have sucsesful grafting persentage and dry weight of shoot higher than ratio 3:1:1 and 1:1:1, (2) NPK fertilizer dosage until 3 g/seedling unsignificant than control on root stock and entres diameter and dry wight of root and shoot; (3) There is no interaction beetwen seedling medium ratio and NPK fertilizer dosage to growth of physic nut seedling by grafting.Key words: grafting, nursery medium, NPK fertilizer, physic nut